Penerapan ISO 31000 dalam Pengelolaan Risiko Pada Bank Perkreditan Rakyat (Studi Kasus Bank Perkreditan Rakyat X) - Tiurma Meilania A. A. D (Business Administration Department - Universitas Katolik Parahyangan, 2014)
AbstractBank is a financial institution and a financial intermediary that accepts deposits andchannels those deposits into lending activities, either directly by loaning or indirectlythrough capital markets. A bank links together customers that have capital deficitsand customers with capital surpluses. There are several types of banks that grows inIndonesia, one of which is the People’s Credit Bank ( BPR). One of the biggest BPRin Indonesia is BPR X.In doing the intermediary function, banks are vulnerable to risk. Therefore, inorder to ensure banks in running its business, a proper risk management is required.Over the time, banks refer to BASEL as risk management reference and guidance butIn practice, managing those risks are not integrated with one another. On this casestudy, we will discuss on how to apply ISO 31000 in risk management on BPR X.The purpose of this ISO 31000 risk management study is to assist banks to integrateand manage all risks across the board and accordance to the principles of ISO31000 which to create and add more values to the company.AbstrakBank adalah lembaga keuangan yang usaha pokoknya adalah menghimpun danadan menyalurkan kembali dana tersebut ke masyarakat dalam bentuk kredit sertamemberikan jasa-jasa dalam lalu lintas pembayaran dan peredaran uang. Terdapatbeberapa jenis bank yang tumbuh di Indonesia, salah satunya adalah Bank Perkred-itan Rakyat (BPR). Salah satu BPR terbesar yang berdiri di Indonesia adalah BPRX.Dalam menjalankan fungsi intermediasi, bank rentan terhadap risiko. Oleh ka-rena itu agar bank lancar dalam menjalankan tugasnya, perlu dilakukan pengelolaanrisiko yang tepat. Selama ini bank menggunakan BASEL untuk mendukung pengelo-laan risiko. Pengelolaan risiko tidak dilakukan secara terintegrasi antara risiko yangsatu dengan yang lain. Maka dari itu pada penulisan studi kasus ini akan dibahasmengenai penerapan ISO 31000 dalam pengelolaan risiko pada BPR X. Tujuan dilakukaannya pengelolaan risiko perbankan berbasis ISO 31000 adalah agar pengelolaan risiko perbankan dapat dilakukan secara menyeluruh dalam perusahaan, dan sesuai dengan prinsip ISO 31000 yaitu mencipkatan dan menambah nilai bagi perusahaan.Keywords: Bank, risk, risk management, ISO 31000